Strategi Marketing Public Relations (Push, Pull, Pass Strategy) Rumah Sakit Islam Surabaya - Alma Nadhila Rahmandani; Triana Setiyarini (Management Department of Economics and Business Of Trunojoyo Madura University, 2022)
This study aims to find out how the Marketing Public Relations Strategy is carried out by the Surabaya Islamic Hospital. The research method used in this study is a qualitative method with a qualitative descriptive type. The sample in this study were 7 respondents consisting of 2 hospital employees and 5 respondents from inpatients. Data collection is done by distributing questionnaires. The results showed that the informants chose RSI Surabaya for treatment because the PKRS (Hospital Health Promotion) activities carried out by the hospital could attract attention and make the informants have confidence in the health services provided by RSI Surabaya. In addition to promoting its health services, RSI is also trying to create a public image through several health talk shows which are broadcast live through PKRS RSI Surabaya media and even broadcast through Suara Muslim Radio 93.8 FM Surabaya.